Біометричний аналіз впливу постійного магнітного поля на насіння дурману звичайного (Datura stramonium L.) - Бено, Юрій; Дика, Марія; Скварко, Костянтин; Beno, Yuriy; Dyka, Mariya; Skvarko, Kostyantyn (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Проведено біометричний аналіз проростання насіння, довжини кореня та стебла дурману звичайного під впливом постійного магнітного поля. Виявлено стимуляційний вплив досліджуваного чинника на схожість на- сіння дурману звичайного. Зміна динаміки проростання насіння, росту коріння та стебел значною мірою зумов- лені різною тривалістю та напруженістю дії постійного магнітного поля. The article contains results of the experimental study of the constant magnetic field effect on seed germination, root growth, stem and leaf surface area Datura stramonium L. Discovered the stimulating effect of constant magnetic field tension 5,0 Е and duration of 0,5 and 15 hours on germination of Datura stramonium L. By the same exposure and field intensity 30,0, 60,0 Е effect of seed germination stimulation was less pronounced. Over 24 hour exposure to the test sensitivity factor seeds were observed, and in 3 hour exposure, we observed inhibition of seed germination. At research of the constant magnetic field influence on the roots growth, stems of Datura stramonium L. stimulating effect was insignificant, which may be explained by the specific features of its sensitivity to the investigated factor. By long-term impact of the magnetic field was observed leaf surface yellowing, that testifies to negative effect of the investigational factors.
Biometric Analysis Early Stages of Development Datura stramonium L. Action under Constant Magnetic Field
Keywords: постійне магнітне поле; дурман звичайний; динаміка проростання насіння; Datura stramonium L.; constant magnetic field; seed germination